Socialization of Qr Code Employee Attendance Applications Based on Android at the Balung Lor Village Office Jember Regency - Reni Umilasari; Amalina Maryam Zakiyyah; Ginanjar Abdurrahman; Teguh Mutawaffi H.F.; Dody Wahyu Wirawan (Kontribusia : Research Dissemination for Community Development, 2022)
Attendance can be said to be a sign of presence which is part of the reporting activities that exist within the institution. Attendance Qr Code is a creative idea to be environmentally friendly or paperless, where the technology is codular-based (website application development). Not only that, the implementation of Google access such as Google forms that use attendance data input and Google Spread sheets for data storage or databases, reporting is easy to manage, because basically Google Spread sheets or Excel can be accessed easily, of course the advantage of using this is free or no cost only with email from Google, no need to buy hosting and domain. So that the control process from the leadership can be carried out properly, the leadership can find out whether the employee is present or not.